Linear and Complex Measures of Heart Rate Variability during Exposure to Traffic Noise in Healthy Women - Myrela Alves; David M. Garner; Anne M. G. G. Fontes; Luiz Vinicius de Alcantara Sousa; Vitor E. Valenti (Complexity)
Previous studies have described significant impact of different types of noise on the linear behavior of heart rate variability (HRV). However, there are few studies regarding the complexity of HRV during exposure to traffic noise. In this study, we evaluated the complexity of HRV during traffic noise exposure. We analyzed 31 healthy female students aged between 18 and 30 years. Volunteers remained at rest seated under spontaneous breathing during 10 minutes with an earphone turned off, and then they were exposed to traffic noise through an earphone for a period of 10 minutes. The traffic noise was recorded from a very busy city street and the sound was comprised of car, bus, and trucks engines and horn (71–104 dB). We observed no significant changes in the linear analysis of HRV. CFP3 (Cohen’s d=1.28, large effect size) and CFP6 (Cohen’s d=1.11, large effect size) parameters of chaotic global analysis and Shannon (Cohen’s d=1.13, large effect size), Renyi (Cohen’s d=1.06, large effect size), and Tsallis (Cohen’s d=1.14, large effect size) entropies significantly increased p<0.005 during traffic noise exposure. In conclusion, traffic noise under laboratory conditions increased the complexity of HRV through chaotic global analysis and some measures of entropy in healthy females.